Clinical Evaluation of the Levels of CEA,CA15-3 and AlphaFeto Protein in Malignant and Benign Pleural Effusion - Marrow, Zina Anwer Salloum; Al-Kassir, Abdul Hammed A.; Al-Sakkal, Nahla Majeed Tawfiq; Khadduri, Julian Dulayl (AL-Kindy College Medical Journal, 2008)
Background: Pleural effusion is a common clinicalproblem.Objective: The aim of the study was to evaluate thediagnostic utility of Carcino embryonic antigen(CEA), CA 15- 3, and alpha-feto protein ( AFP ) asa tumor markers in serum and pleural effusion andevaluate the value of combining them as a diagnostictools that are complementary to cytology in thediagnosis of malignancies .Methods: Forty patients (18 malignant and 22 benignpleural effusion) were included in this study .Theserum and effusion levels of CEA, CA 15 – 3 andAFP were measured using immunoradiometric assayResults: from the 40 effusions studied 26 wereexudates and 14 were transudates. The level ofpleural effusions of CEA, CA 15 – 3 and AFP wereincreased above the cutoffs in 72.5%, 94.4 % and 5.5% of tested samples with malignancies respectively.A direct strong significant correlation between serumand pleural fluid CEA, CA 15 – 3 and AFP wasnoted.Conclusion: Pleural effusion CEA is the mostaccurate marker for the diagnostic separation ofmalignant and benign. The combination of both CEA,CA 15 – 3 improves the sensitivity by up to 11 %.AFP has no role in the process